2012
DOI: 10.5152/akd.2012.043
|View full text |Cite
|
Sign up to set email alerts
|

The effects of implanted valve sizes on ventricular hypertrophy in aortic stenosis

Abstract: Objective: We aimed to study the effects of the valve sizes according to body surface area on aortic gradient and ventricular hypertrophy in the cases of aortic valve replacement due to isolated aortic stenosis. Methods: Between January 2006 and April 2007, patients (12 men, 15 women; totally 27) followed up prospectively with echocardiography fourth and sixth month postoperatively. The patients were divided into two groups according to the prosthetic aortic valve diameters (19-21 mm vs 23-25 mm). The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Surgical approach is still the gold standard for the management of the aortic valve pathologies. [1][2][3][4][5][6][7][8][9][10][11][12] Bioprosthetic valves are preferred to replace the aortic valves of the patients aged above 65 years. The overall mortality of isolated aortic valve replacement is nearly 3.5% in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Surgical approach is still the gold standard for the management of the aortic valve pathologies. [1][2][3][4][5][6][7][8][9][10][11][12] Bioprosthetic valves are preferred to replace the aortic valves of the patients aged above 65 years. The overall mortality of isolated aortic valve replacement is nearly 3.5% in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[4] After all, it has been noted that PPM can be largely avoided using the correct preventive strategy at the time of operation both for sAVR and TAVI. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In surgery, the incidence of PPM can be reduced by choosing the correct size of bioprosthesis, using stentless bioprosthesis, supra-annular implantation of the valve, aortic root manipulations or extensions, considering the left ventricular EF, BSA, age, and gender of the patient during operation. Recent studies have also demonstrated that allografts, homografts, and stentless bioprostheses have less gradient differences inversely greater EOA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations